2013
DOI: 10.1149/2.019304jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volatile Boron Species on the Electrocatalytic Activity of Cathodes of Solid Oxide Fuel Cells

Abstract: The effect of volatile boron species on the electrocatalytic activity, microstructure and phase stability of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) cathodes has been studied. The cathodes were heat-treated at 800 o C for 7 days in air in the presence of boron species vaporized from borosilicate glass, and were characterized by EIS, SEM, AFM, SIMS, XRD, XPS and ICP-OES. The results have shown that after the heat-treatment in the presence of borosilicate glass, boron deposition occurs mainly on the region near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 74 publications
0
38
0
Order By: Relevance
“…Many studies have been devoted to investigating LSCF degradation and several causes have been reported, among them: i) mutual cations diffusion between interfaces with consequent atoms depletion and phase separation, [11][12][13][14][15][16] ii) LSCF grain coarsening, 17 iii) reactivity with YSZ-based electrolytes, even with ceria-based barrier layer, 18 iv) impurity contamination, namely Cr from metal interconnects and B from sealing when the cell is inside a stack. [19][20][21] Some recent work performed on an LSCF/CGO (Ce 0.9 Gd 0.1 O 2-δ ) composite cathode on a YSZ electrolyte with a CGO barrier layer 11 affirms that Sr depletion, phase separation and cations inter-diffusion occur mainly during the fabrication process, with negligible contributions during long-term operation (973 K). On the other hand, some previous works conversely found that LSCF cathode degradation also occurs during long-term testing, although that works was generally carried out at temperatures higher than the temperature investigated in this paper (973 K).…”
mentioning
confidence: 87%
“…Many studies have been devoted to investigating LSCF degradation and several causes have been reported, among them: i) mutual cations diffusion between interfaces with consequent atoms depletion and phase separation, [11][12][13][14][15][16] ii) LSCF grain coarsening, 17 iii) reactivity with YSZ-based electrolytes, even with ceria-based barrier layer, 18 iv) impurity contamination, namely Cr from metal interconnects and B from sealing when the cell is inside a stack. [19][20][21] Some recent work performed on an LSCF/CGO (Ce 0.9 Gd 0.1 O 2-δ ) composite cathode on a YSZ electrolyte with a CGO barrier layer 11 affirms that Sr depletion, phase separation and cations inter-diffusion occur mainly during the fabrication process, with negligible contributions during long-term operation (973 K). On the other hand, some previous works conversely found that LSCF cathode degradation also occurs during long-term testing, although that works was generally carried out at temperatures higher than the temperature investigated in this paper (973 K).…”
mentioning
confidence: 87%
“…[1][2][3][4][5][6][7][8] Among them, gaseous chromium species vaporized from the chromium oxide scale of chromia-forming metallic interconnect are probably the most investigated contaminants affecting the performance of SOFCs' cathodes. The mechanism and process of the deposition and poisoning of chromium species at the cathodes of SOFCs have been extensively investigated, including LSM, [9][10][11] LSCF 12 and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF).…”
mentioning
confidence: 99%
“…[18][19][20][21] Boron is chemically incompatible with the cathode materials, and preferentially reacts with the A-site cations in particular lanthanum to form insulating lanthanum borate, LaBO 3 . 22 The reaction between boron and LSM to form LaBO 3 is generally slow under open circuit conditions.…”
Section: -3mentioning
confidence: 99%
“…20 Compared to LSCF, La-free BSCF cathode is more resistant to boron poisoning. Boron deposition mainly occurs in the outmost electrode layer of the BSCF cathode, while the inner region close to the electrode/electrolyte interface is relatively intact and still functions electrochemically.…”
mentioning
confidence: 99%